Analisis Strategi Pemasaran Usaha Tempe Di Bekasi - Eva Ariyanti; Wahidin Septa Zahran (JAMBIS : Jurnal Administrasi Bisnis, 2021)
Based on the data from Ministry of Agriculture, soybean import from 2015 to 2018 kept getting increased. In 2015 and 2016, was recorded soybean import of 2.3 million tons, 2017 2.7 million tons, and experienced a slight decrease in 2018 into 2.6 million tons. Soybean import dependence caused high price of soybeans that made Micro, Small and Medium Enterprise (MSME), such as Mr. Tochari, have to manage overcome it. The study aimed to analyze the marketing strategies, the obstacle faced, and to formulate the efforts to be taken by the enterpreneur to improve the marketing strategies. The study implemented descriptive qualitative method. While the data collection techniques used were observation, interview, and documentation. The result of the study showed that the marketing strategies implemented by the tempe enterpreneur Mr. Tochari through marketing mix (4P) and SWOT Analysis mostly reached the targets, but there were some obstacle, namely dependence on soybean import, production tools that could not fulfill all of the needs in one production process so it required loner time, and production process that still implemented traditional way